Decreased serum homocysteine levels after micronutrient supplementation in older people - Pusparini, Pusparini (Faculty of Medicine, Trisakti University, 2010)
Aging is associated with a gradual impairment in cognitive function. The elderly also show a high prevalence of undernutrition, whereas nutrition plays an important role in the metabolism of neuronal cells and enzymes. Homocysteine is an amino acid resulting from methionine metabolism and is dependent on intake of vitamin B12, vitamin B6 and folic acid. Homocysteine is said to play a role in cognitive function. The objective of this study was to evaluate the effect of micronutrient supplementation for 6 months on serum homocysteine levels and cognitive function in older people. This study was an experimental study of pre-post test design, carried out in Mampang subdistrict, South Jakarta. A total of 94 elderly people was recruited for this study, consisting of 44 females and 50 males. Serum homocysteine level was assessed by fluorescent polarization immunoassay and cognitive function by means of the mini mental state examination (MMSE) before and after micronutrient supplementation. Mean serum homocysteine concentration after supplementation decreased significantly to 14.8 ± 5.8 mmol/L, compared with mean serum homocysteine level of 15.9 ± 5.9 mmol/L before supplementation (p=0.000). Multiple regression analysis indicated that the factors influencing post-supplementation MMSE scores were gender (â=-0.350; p=0.000), education (â=0.510; p=0.000) and post-supplementation homocysteine levels (â=-0.201; p=0.000), while age, pre-supplementation homocysteine levels and BMI did not affect MMSE scores. Homocysteine concentration decreased significantly after 6 months of supplementation. The factors affecting post-supplementation MMSE scores were gender, level of education, and post-supplementation homocysteine level.